2005
DOI: 10.1063/1.2080027
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on magnetic circular dichroism by the finite perturbation method with relativistic corrections

Abstract: A theoretical method for calculating magnetic circular dichroism (MCD) of molecules is presented. We examined the numerical accuracy and the stability of the finite perturbation (FP) method and the sum-over-state (SOS) perturbation method. The relativistic effects are shown to be important for the MCD spectra of molecules containing heavy elements. Calculations using the FP and the SOS methods were carried out for ethylene, para- and ortho-benzoquinone, showing that the FP method is superior to the SOS method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 53 publications
0
33
1
Order By: Relevance
“…The SFR+ SO1 + SO2 result by Honda et al 32 is found to be significantly lower ͑2.88 eV͒, whereas the value found by Roszak and Lipinski for this state is considerably higher ͑3.38 eV͒ compared with our MRCISD+ Q result.…”
Section: +09contrasting
confidence: 55%
See 1 more Smart Citation
“…The SFR+ SO1 + SO2 result by Honda et al 32 is found to be significantly lower ͑2.88 eV͒, whereas the value found by Roszak and Lipinski for this state is considerably higher ͑3.38 eV͒ compared with our MRCISD+ Q result.…”
Section: +09contrasting
confidence: 55%
“…[20][21][22][23][24][25] The first ab initio potential curves for the Cl 2 molecule were computed by Peyerimhoff and Buenker 26 more than 25 years ago under the ⌳-⌺ approximation and served as the mainly theoretical basis for analysis of experimental data. Although semiempirical relativistic intermediate neglect of differential overlap ͑INDO͒ calculations were performed in Cl 2 15 years ago, 27 only recently, ab initio calculations including spin-orbit coupling have been performed [28][29][30][31][32][33] for some low lying valence states ͑usually͒ applying a relativistic core potential approach. Therefore, high accurate theoretical potential curves are of interest to understand Cl 2 spectra, as well as the analysis of nonadiabatic processes 34 and experimental data regarding the Cl 2 dissociation.…”
mentioning
confidence: 99%
“…4,6,11,16, so-called complex polarization propagator (also known as damped response theory) methods 12,13,20 -as well as realtime methods 21 -have emerged in the last decade along with modern versions of sum-over-states approaches; 22,23 relativistic schemes have also been proposed. 24 We refer to Refs. 10 and 17 for reviews up to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…SOS computational methods have been used relatively extensively for MCD computations in the past and are generally believed to be inconvenient for routine computations as they involve lengthy configuration interaction procedures . However, as shown below, this is not true for accurate excited states obtained from the TDDFT.…”
Section: Introductionmentioning
confidence: 99%